1982
DOI: 10.1016/s0047-2484(82)80008-0
|View full text |Cite
|
Sign up to set email alerts
|

The fayum primate forest revisited

Abstract: The Faywn Prim.ate Forest RevisitedIn Oligocene times, the Fayum area of northern Egypt was a subtropical to tropical lowland coastal plain with damp soils and seasonal rainfall that supported an abundance and variety of vegetation, including lianes (large vines), tall trees, and possibly mangroves, and a large and varied vertebrate fauna. The Oligocene marine strandline was close by and principal Jebel Qatrani Formation streams were probably brackish several kilometers inland due to tidal incursions.Sediments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 175 publications
(55 citation statements)
references
References 35 publications
1
53
0
Order By: Relevance
“…Ten species of angiosperm wood were reported from probable lower Paleocene marginal marine sediments in Niger (Koeniguer, 1971), but the oldest diverse flora of large angiosperm trunks is from the early Eocene of Wyoming, U.S.A. (Wheeler et al, 1977(Wheeler et al, , 1978. Among many diverse assemblages of large angiosperm trunks in the later Tertiary are those from the Oligocene of Egypt (Kr~iusel, 1939;Bown et al, 1982), and the Miocene of the northwestern U.S.A. (Prakash and Barghoorn, 1961).…”
Section: Angiosperm Staturementioning
confidence: 99%
“…Ten species of angiosperm wood were reported from probable lower Paleocene marginal marine sediments in Niger (Koeniguer, 1971), but the oldest diverse flora of large angiosperm trunks is from the early Eocene of Wyoming, U.S.A. (Wheeler et al, 1977(Wheeler et al, , 1978. Among many diverse assemblages of large angiosperm trunks in the later Tertiary are those from the Oligocene of Egypt (Kr~iusel, 1939;Bown et al, 1982), and the Miocene of the northwestern U.S.A. (Prakash and Barghoorn, 1961).…”
Section: Angiosperm Staturementioning
confidence: 99%
“…These arguments were vitiated by Bown et al (8) based on evidence from Iitholog\', sedimentology, fossils of plants, vertebrates, and invertebrates, and finally from the structural adaptations of the primates themselves. They concluded that the Jebel Qatrani Formation was deposited near the coastline of the Tethyian seaway with interdigitating habitats of estuarinc mangroves, fresh and brackish fluviatile swamps, and forested floodplains flourishing in a climate "typified by adequate, though probablv seasonal rainfall" (8).…”
Section: The Early Oligocene Fossil De-mentioning
confidence: 99%
“…Snow does not report any osprey specimens from this area, but there are sight and breeding records for ospreys from the Ugandan shore of Lake Victoria {17, 18). The only species absent from this area are the flamingos, which require shallow bodies of saline or brackish water, although flamingos do occur in the rift systems that flank Lake Victoria on the east and west, and esmarine environments probably suitable for modern-type flamingos occurred near the site of deposition of the Fayum fossils {6, 8).…”
Section: The Early Oligocene Fossil De-mentioning
confidence: 99%
“…The central geographic position of the Fayum of Egypt with respect to modern lorisiform distribution underscores the likelihood that the region played an important role in early lorisoid evolution. The presence in the Fayum of an early representative of both the Lorisidae and Tarsiidae, the only two prosimian families still extant in Asia, adds to the evidence indicating faunal and floral similarities between the Oligocene Fayum and modern South Asia, as documented also by plants such as the liane Epipremnum, and the crocodilian Tomistoma (Bown et al, 1982).…”
Section: The Fayum Lorisidmentioning
confidence: 69%